Hydrogels for Biomedicine Based on Semi-Interpenetrating Polymeric Networks of Collagen/Guar Gum: Synthesis and Physicochemical Characterization - Lopéz-Martínez, Edith E.; Claudio-Rizo, Jesús A.; Caldera-Villalobos, Martín; Becerra-Rodríguez, Juan J.; Cabrera-Munguía, Denis A.; Cano-Salazar, Lucía F.; Betancourt-Galindo, Rebeca (Macromolecular research, 2022)
Novel synthetic strategies to produce biopolymer based hydrogels for biomedical applications are required currently. Collagen hydrogels for wound healing can improve their structural and physicochemical properties by incorporating polysaccharides within the fibrillar matrix. Novel hydrogels were synthesized by semi-interpenetration of guar gum (GG) in a matrix of crosslinked collagen with hydrophilic polyurethane. GG concentrations of 10, 20, 30, and 40 wt% on the semi-IPN matrices were tested. The addition of the polysaccharide accelerates the gelling time of the hydrogels; 30 wt% of GG allows a 68 ± 5% of physicochemical crosslinking, exhibiting a maximum swelling of 3496 ± 89% and both improved mechanical and thermal resistance. The short-range interactions established in these matrices, mainly of the hydrogen bond type, make it possible to delay their hydrolytic and proteolytic degradation. The structure and properties of these hydrogels could have potential application in biomedicine as dressings for chronic wound healing, tailoring the controlled release of drugs with therapeutic interest, cell viability and proliferation, cell signaling, hemocompatibility and antibacterial character.